Cocoa extract has activity on selectively killing of breast cancer cells line - ariza budi tunjung-sari; Mahriani Mahriani; Gusti Agung Perias Tiningrum; Teguh Wahyudi; Misnawi Jati (Journal of Tropical Life Science, 2015)
Effect of the cocoa crude extract on mortality of breast cancer cell lines i.e. MCF-7, T47D and normal cell (Vero), was observed. Crude cocoa extract prepared from a freshly dried cocoa bean that was containing 14% catechin and 0.6% caffeine. Catechin and caffeine content were modulated to 2-folds (28% catechin or 1.2% caffeine) and 3-folds (42% catechin or 1.8% caffeine) by adding pure compounds. Extracts were dissolved in dimethylsulfoxide (DMSO) at concentrations ranging from 200 to 1600 Î¼g/ml. The positive control was doxorubicin (0.5-16 Î¼g/ml in DMSO). Cell lines (MCF-7, T47D, and Vero) were incubated in test sample for 24h at 37Â°, prior to 3-(4,4-dimetylthiazole-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The absorbance of each well was measured at 550 nm, and lethal concentration (LC50) was calculated. The cocoa extract induced mortality of breast cancer cell lines but not in Vero cells. The effect on MCF-7 was greater than on T47D, given the LC50 was 1236 Î¼g/ml (MCF-7) and 1893 Î¼g/ml (T47D). Cytotoxic potential of cocoa extract was much lower than doxorubicin whose LC50 was0,777 Î¼g/ml (MCF-7) and 0,082 Î¼g/ml (T47D). Increasing catechin content to 2-folds did not significantly affect LC50 value, but 3-folds catechin content reduced LC50 to 1021 Î¼g/ml. Meanwhile increasing caffeine content to 2-folds significantly reduced LC50 to 750 Î¼g/ml, however, 3-fold content resulted in slightly higher LC50 at 780 Î¼g/ml. This indicates that cocoa extract have anti-cancer potential, and purification may improve this property .